The Legal Reform of Trademark Protection and Dispute Mitigation: Lessons From Licensing Well-Established Brands in Indonesia - Agung Sujatmiko; Mochamad Kevin Romadhona; Patrick Keizer; Christoph Antons (Journal of Law and Legal Reform, 2024)
This paper explores the intricate landscape of trademark protection within the realm of Intellectual Property Rights (IPRs). Trademarks, emblematic of brand identity and consumer trust, wield significant economic value and reputation. However, they are increasingly vulnerable to infringement, posing challenges to both proprietors and regulatory bodies. Against this backdrop, the efficacy of license agreements as a mechanism for mitigating trademark infringement is examined. Through a comprehensive analysis of contract law principles, including freedom of contract and good faith, this study elucidates strategies for bolstering trademark protection. Drawing upon legislative frameworks, contextual analysis, and case law, the paper proposes a nuanced approach to navigating trademark-related disputes. By fostering transparent and mutually beneficial relationships between brand owners and licensees, this framework seeks to uphold the integrity of trademarks while safeguarding market integrity. Ultimately, the paper advocates for a collaborative effort among stakeholders to ensure equitable practices and uphold the sanctity of trademarked goods and services in the global marketplace.